Capabilities Welfare: Educational Response to Challenge Post-pandemic Poverties - Oscar Tiozzo Brasiola; Sara Baruzzo (Pensa MultiMedia, 2022)
The pandemic situation has fueled numerous debates and reflections not only in the health but also in the educational field. The period of multiple crisis we are going through shows with increasingly clear scientific evidence that the welfare paradigm is no longer able to offer adequate responses to the new post-pandemic challenges. It is necessary to formulate other possible models such as generative welfare and the welfare of capabilities, aware that these transformations we are going through must be supported by didactic approaches different from those used up to now. Putting educational and planning co-responsibility back at the center becomes the sine qua non for taking advantage of this period of crisis and transform it in a period of opportunity.